Peran Komunikasi Direktorat Samapta Bhayangkara Kepolisian Daerah Kalimantan Tengah (Ditsabhara Polda Kalteng) Dalam Peningkatan Patroli Dialogis Di Kota Palangka Raya: Communication Role Of Directorate Samapta Bhayangkara Police Of Central Kalimantan Region (Ditsabhara Polda Kalteng) In The Improvement Of Dialogis Patrol In The City Palangka Raya - Junaidi, Junaidi; Utama, Dwi Priya (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2019)
This research aims to explain and describe the communication role of the Directorate of Samapta Bhayangkara Police of Central Kalimantan region (Ditsabhara Polda Kalteng) in the improvement of Dialogical patrol in the city Palangka Raya. The research methods used are qualitative, using data collection techniques through observation, interviews, and documentation. The data sources in this research are members of Subditgasum Ditsabhara Polda Kalteng and some of the communities in the city of Palangka Raya. Based on the research of Communication role of Directorate Samapta Bhayangkara Police of Central Kalimantan region (Ditsabhara Polda Kalteng) in the improvement of Dialogical patrol in the city Palangka Raya is good enough, but the response from the community in Provide information still not good. Researchers have indicated that the Directorate of Samapta Bhayangkara Polda Kalteng in this matter through Subdit Gasum as a patrol officer has been doing its role in patrolling as a preventive effort and minimize the disturbance of the Kamtibmas well. However, in the implementation of police patrol tasks get barriers from the community in the form of lack of responses and information provided by the community itself to support the situation of the environment that remains conducive.